Is a top level ontology based digital twin the solution to human-machine interoperability? - D’Amico, Rosario Davide; Addepalli, Sri; Erkoyuncu, John Ahmet (SSRN, 2022)
Over the last decade, life cycle management has made leaps and bounds not just enhancing but also creating newer interactivity with the modelling world. A digital twin (DT) monitors the condition of the mirrored entity through life, providing a holistic overview of both its functionality and operability. Whilst DTs are gaining interest, the current challenge in their efficient utilisation is the interoperability between those different DTs. Today, DTs are being created for domain-specific functionalities (closed architectures), often using proprietary solutions, limiting their interoperability. This paper aims to present a high-level DT framework based on a standard top-level ontology called the Basic Formal Ontology (BFO) as a solution to the integration of twins. BFO is a well-established top-level ontology in the biomedical sector, as it is the core of the Open Biological Ontologies (OBO) Foundry. This paper contains a review of the state-of-the-art DTs based on top-level ontologies and highlights the value of implementing this framework, especially in the maintenance phase. The proposed open framework enables and improves the interoperability of DTs, creating the fundamental infrastructure where DTs can work together in a federation of twins. This research is an attempt to identify the applicability of this fundamental, interdisciplinary, cross-sectoral linkage for digitally enhanced eMaintenance platforms and their effective deployment. The paper thus presents an overview of how a typical BFO based DT would work in the context of a network of twins that targets human-in-the-loop (HITL) and their interoperability establishing a future towards the next industrial revolution: Industry 5.0.
Keywords: Digital twin; ontology; BFO; network of twins; eMaintenance; industry 5.0; industrial ontology foundry (IOF); semantic